2015
DOI: 10.1186/s13045-015-0132-6
|View full text |Cite
|
Sign up to set email alerts
|

YM155 potently kills acute lymphoblastic leukemia cells through activation of the DNA damage pathway

Abstract: BackgroundNovel-targeted therapies are in rapid development for the treatment of acute lymphoblastic leukemia (ALL) to overcome resistance and decrease toxicity. Survivin, a member of the inhibitor of apoptosis gene family and chromosome passenger complex, is critical in a variety of human cancers, including ALL. A well-established suppressor of survivin has been the small molecule, YM155. Reports are identifying other mechanisms of action for YM155. Therefore, we sought to investigate the mode of action and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 32 publications
3
25
1
Order By: Relevance
“…It was also in phase II clinical trials for malignant conditions in young patients such as refractory CNS malignancies 17 . YM155 causes downregulation of survivin and the induction of DNA damage 18, 19 , and it was evaluated in various clinical trials for single and combination therapy in prostate cancer, lymphoma and melanoma 20, 21 .
Figure 1YM155 and lapatinib show high degree of synergy in neuroblastoma regardless of the MYCN and TRKA status. ( A ) Overview of the drug library used in the concentration matrix-based combination screen.
…”
Section: Resultsmentioning
confidence: 99%
“…It was also in phase II clinical trials for malignant conditions in young patients such as refractory CNS malignancies 17 . YM155 causes downregulation of survivin and the induction of DNA damage 18, 19 , and it was evaluated in various clinical trials for single and combination therapy in prostate cancer, lymphoma and melanoma 20, 21 .
Figure 1YM155 and lapatinib show high degree of synergy in neuroblastoma regardless of the MYCN and TRKA status. ( A ) Overview of the drug library used in the concentration matrix-based combination screen.
…”
Section: Resultsmentioning
confidence: 99%
“…YM155 is a small-molecule survivin suppressor that distinctly interacts with the survivin core promoter region of 269 base pairs, specifically inhibiting the expression of survivin (4,53). YM155 has effects on gene expression and phosphorylation (54). A certain study demonstrated that YM155 effectively inhibited the expression of survivin mRNA in SGC-7901 and MKN-28 cells in a dose-dependent manner (55).…”
Section: Recent Therapeutic Approachesmentioning
confidence: 99%
“…Chang et al (54) suggested that patients need to be pre-selected for YM155 sensitivity to guarantee beneficial outcomes. Their findings confirmed that YM155 is an ideal candidate drug for therapeutic regimens when administered to a certain subgroup of patients (54). Further study is required to identify the underlying mechanism of selective sensitivity to YM155 in cancer cells.…”
Section: Recent Therapeutic Approachesmentioning
confidence: 99%
“…YM155 (sepantronium bromide) was introduced as a transcriptional suppressor of survivin expression that displayed activity against a broad range of cancer types in preclinical models. 1, 3 However, further studies suggested that the YM155-induced inhibition of survivin expression may be a secondary effect downstream of YM155-induced DNA damage 1, 4, 5 or associated with Myeloid Cell Leukemia 1 (Mcl-1) depletion. 6 …”
mentioning
confidence: 99%